Distúrbios da oralidade na melancolia - Magtaz, Ana Cecilia (2008)
This doctoral thesis goes into theoretical-clinical issues treated earlier in the master's dissertation entitled Psychoanalytic approach to anorexia and bulimia as disorders of orality. The dissertation was defended in 1998 in the context of the laboratory of Fundamental Psychopathology of the Center for Psychoanalysis in the Graduate Study Program in Clinical Psychology at the Catholic University of São Paulo. This thesis does not have the objective of defending any classificatory structural position related to the need for a differential diagnosis of anorexia and bulimia as clinical entities. It will defend the perspective that disorders of orality are symptomatic manifestations of melancholia, a narcissistic neurosis. This perspective does not rule out the possibility of there also being disorders of orality in other defensive structures, such as in hysteria or perversion. In other words, anorexia, bulimia, obesity and addictions in general are symptomatic expressions that can occur in melancholic dimensions of the transference neuroses and of perversion. The superego being a structural dimension of the psychic apparatus, the shadow of the object can fall on the ego, regardless of the subject's psychopathological structure. This means that narcissistic neurosis has dynamics that are relatively independent of the transference neurosis where, contrary to narcissistic neurosis, the conflict takes place between id and ego